Biostimulant activity of Galaxaura rugosa seaweed extracts against water deficit stress in tomato seedlings involves activation of ABA signaling - Sarai Morales-Sierra; Juan Cristo Luis; David Jiménez-Arias; Nereida M. Rancel-Rodríguez; Alberto Coego; Pedro L. Rodriguez; Mercedes Cueto; Andrés A. Borges (Frontiers in Plant Science, 2023)
Water scarcity is a serious constraint for agriculture, and global warming and climate change can exacerbate it in many areas. Therefore, sustainable approaches must be implemented to deal with current and future water scarcity scenarios. Genetic and chemical approaches are being applied to manage this limitation and maintain crop yields. In particular, biostimulants obtained from natural sources such as marine algae are promising aids for coping with water deficit stress in agriculture. Here we present a bioprospection study of extracts of the macroalgae Bonnemaisonia hamifera, Galaxaura rugosa, Dasycladus vermicularis, Ulva clathrata, Cystoseira foeniculacea, Cystoseira humilis, Lobophora dagamae, Colpomenia sinuosa and Halopteris scoparia from the north coast of Tenerife, in the Canary Islands. The aqueous extracts of Bonnemaisonia hamifera, Galaxaura rugosa, Dasycladus vermicularis and Cystoseira humilis show biostimulant activity against water deficit stress in tomato seedlings under controlled conditions, providing higher tolerance than the mock-treated control. The Galaxaura rugosa extract showed the highest biostimulant activity against water deficit stress. We demonstrate that this positive effect involves the activation of the abscisic acid (ABA) pathway in Arabidopsis thaliana (arabidopsis) and Solanum lycopersicum (tomato). Application of G. rugosa extract to the root system by drenching tomato seedlings subjected to water deficit leads to improved CO2 assimilation and water use efficiency (WUEp), compared to mock-treated plants. These results highlight a new potential seaweed source of substances with osmoprotectant properties, useful for biostimulant development. Future studies may provide further insight into which components of the seaweed extract induce activation of the ABA pathway.